Students' Capability In Writing Recount Text Of The First Year Students Of SMA Negeri I Cepogo, Boyolali In 2011/2012 Academic Year - Kurniawati, Dian Sari; , Aryati Prasetyarini, S.Pd, M.Pd; , Dra, Dwi Haryanti. M. Hum (2013)
The aims of this research is to know the students' capability in writing recount text of the first year students of SMA Negeri I Cepogo, Boyolali 2011/2012 Academic year, to know the problems faced by the students in writing recount text, and to know the causes of the problem This research is an explorative descriptive research. The methods of collecting data are observation, interview, and document. Data of the research are the document and interview. Data source of the research is the students' writing of recount text. The technique of data analysis is (1) collecting the data taken from the observation and interview. (2)analyzing the data based on five criterias of writing recount text. (3) classifying the data based on the score, and (4) drawing conclusion. Based on the analyzed data, it can be concluded that the students' capability in writing recount text of the first year students of SMA Negeri I Cepogo, Boyolali is categorized in four grades. There are 2 students in excellent grade or 4, 54%. The students in good grade are 12 students or 27, 27 %. In fair grade, there are 22 students or 50%. In poor grade there are 8 students or 18, 18%. The problem faced by the first year students in writing recoun text is (1)the students feel difficult to express their idea. (2) the low mastery of English grammar. (3) the lack of the vocabulary. The cause of the problem are (1)the students' background.(2) Less of the eager of improving the writing capability,(3) students still depend on the guided of the English teacher in writing.